The 'tragedy' of Charlie Gard: a case study for regulation of innovation?. Issue 1 (2nd January 2019) - Montgomery, Jonathan
ABSTRACT: Reflections on the Charlie Gard litigation suggest that procedural regulation is important to prevent tragic cases becoming 'tragedies'; where well-intentioned but overconfident doctors and parents conflict in ways that are deeply destructive.